Three new species of the genus Thrips (Thysanoptera, Thripidae) in Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2019)
A revised key is provided to 33 species of the genus Thrips recorded from Japan, including the descriptions of three new species, T. rhamni, T. shiranensis, T. unisetifer.